(untitled) (Revista Brasileira de Contabilidade e Gestão, 2019)
In Brazil’s innovation system, there are several actors. Thus, the objective of this paper is to present the institutions and interaction flows present in the Brazilian innovation system. To this end, we use a bibliographic and documentary review. As a result, it can be understood that there are several institutions in the country that corroborate the national C, T & I, where the greatest flow of interaction is present between government (promotion), large companies and ICT’s. Finally, be noted that Brazil still has a long way to go to developed economies.